Edukasi dan Pelatihan Terkini Senam Pencegah Stroke serta Perawatan Sendi bagi Lansia - Afifah Noer; Hasni Dyah Kurniawati; Aisyah Rahmadhani; Syafira Izzatul Jannah; Abdullah Nur Afghani Gymnasdiar (Lembaga Pengembangan Kinerja Dosen, 2026)
Older adults represent a vulnerable population who experience gradual functional decline as part of the aging process, increasing their susceptibility to non-communicable diseases such as stroke and joint problems. Insufficient physical activity and limited understanding of suitable exercises for seniors often lead to decreased fitness levels and diminished quality of life. This community service initiative was designed to enhance elderly well-being through education and training on stroke-preventive exercises and joint care, conducted at the Posyandu Lansia in Plosorejo Village, Matesih District, Karanganyar Regency. The program involved free health screenings, educational sessions using leaflets and video presentations, and guided demonstrations of elderly exercise routines. Evaluation was performed through observation and group discussions to measure participants’ comprehension. Findings revealed strong engagement among participants and a notable increase in awareness regarding the importance of regular exercise for stroke prevention and joint health. Overall, the program successfully promoted better health awareness and improved quality of life for the elderly community.